2014
DOI: 10.1002/phar.1462
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Medication-Related Problems among Medicaid Patients Participating in a Pharmacist-Provided Telephonic Medication Therapy Management Program

Abstract: Study Objective To identify predictors of medication-related problems (MRPs) among Medicaid patients participating in a telephonic medication therapy management (MTM) program. Design Retrospective analysis of data from patients enrolled in a previously published study Data Sources Two Medicaid administrative claims file databases (for healthcare utilization and prescription dispensing information) and one pharmacy organization file for MTM program information. Patients Seven hundred twelve adult Medicaid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
(58 reference statements)
6
9
0
Order By: Relevance
“…Such findings are in accordance with several studies showing low adherence and persistence in asthma patients . In contrast, Snyder et al reported a lack of predictors in their adherence‐specific problems, possibly because of an insufficient number of asthma patients. Interestingly, although potential/actual adverse reactions were observed in more than a third of the patients involved in medication reviews, there was no particular medication or indication associated with this DRP.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Such findings are in accordance with several studies showing low adherence and persistence in asthma patients . In contrast, Snyder et al reported a lack of predictors in their adherence‐specific problems, possibly because of an insufficient number of asthma patients. Interestingly, although potential/actual adverse reactions were observed in more than a third of the patients involved in medication reviews, there was no particular medication or indication associated with this DRP.…”
Section: Discussionsupporting
confidence: 91%
“…The count of medications and indications were predictors of the quantity of DRPs, which was expected and in line with literature data . We identified possible risk factors for most DRPs.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…15,16 In 2012, to be eligible for MTM services, beneficiaries had to have 2–3 chronic diseases, take 2–8 Part D drugs, and exceed a drug cost threshold of inflation-adjusted $3,100.20. 16 In addition to the Medicare Part D program, non-Medicare insurance programs for populations other than Medicare beneficiaries also have offered MTM programs and used similar eligibility criteria for MTM services as Medicare Part D. 6,7,1720 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies have found somewhat limited utility of these criteria as predictors of MRPs and opportunities for improvements in MTM eligibility criteria. 8-10 …”
Section: Introductionmentioning
confidence: 99%